Running the World's Markets : The Governance of Financial Infrastructure - Lee, Ruben (Book collections on Project MUSE., 2011)
The efficiency, safety, and soundness of financial markets depend on the operation of core infrastructure--exchanges, central counter-parties, and central securities depositories. How these institutions are governed critically affects their performance. Yet, despite their importance, there is little certainty, still less a global consensus, about their governance. Running the World's Markets examines how markets are, and should be, run. Utilizing a wide variety of arguments and examples from throughout the world, Ruben Lee identifies and evaluates the similarities and differences between ex.